The Effect Of Sp6 Acupressure Massage On Menstrual Pain Reduction In Female Students In Grade X At SMAN 1 Bengkulu City In 2024 - Oktaviani, Anggi; Azissah, Danur; Tranado, Hengki (Journal Hygeia Public Health, 2025)
Data from the World Health Organization (WHO) shows that 90% or 1,769,425 women experience dysmenorrhea, with 10-15% experiencing severe dysmenorrhea. In Indonesia alone, the figure reaches 64.25% among women of reproductive age, which can interfere with daily activities for 1-2 days each month. Many women in Indonesia experience dysmenorrhea but do not seek treatment or management and tend to ignore it. The aim of this study is to determine the effect of acupressure massage on the Sp6 point on reducing menstrual pain among female students in Grade X at SMAN 1 Kota Bengkulu in 2025. The research method used is a quasi-experimental design with a one-group pretest-posttest design. The sampling technique used was purposive sampling, with a sample size of 68 female students in Grade X at SMAN 1 Kota Bengkulu. The results of the univariate analysis before the Sp6 acupressure massage intervention showed that most respondents (73.5%) experienced moderate pain. After the acupressure massage intervention at the SP6 point, most respondents (79.4%) reported mild pain. The bivariate analysis revealed a significant effect of acupressure massage at the SP6 point on reducing menstrual pain (p=0.000). There is an effect of acupressure massage at the Sp6 point on reducing menstrual pain in female students in Grade X at SMAN 1 Kota Bengkulu in 2025. The researcher suggests that SMAN 1 Kota Bengkulu can enhance the knowledge of female students at the school through educational efforts regarding interventions that can be implemented to reduce menstrual pain in female students.